ENERGY AND CONSTRUCTION CONDITIONS OF THE EFFECTIVENESS OF APPAATUS FOR GENERAL CRYOTHERAPEUTIC IMPACT - A. U. Baranov; A. A. Osinа; V. A. Sinkova (Вестник Дагестанского государственного технического университета: Технические науки)
Objectives. To evaluate the correspondence of construction and power consumption of Cryotherapeutic Complexes (CTC) with technological conditions of effectiveness of the General Cryotherapeutic Impact (GCI). Methods. The associated analysis method used Cryotherapeutic Complexes (CTC) construction and power consumption with technological conditions of effectiveness of the General Cryotherapeutic Impact (GCI). Results. An explanation for the discrepancy of observations of different researchers in differences in design and available power of the CTC is proposed. The technical operating characteristics of single-seat and multi-seat CTC are provided and these significant differences in apparatus of identical technological designation are illustrated. The proposed system of specific CTC characteristics is capable of unifying their basic structural and energy characteristics. Calculation of the specific characteristics of existing systems showed that between objects of the same designation, there are differences in value, which may be the cause of discrepancies in their therapeutic efficacy. All functional CPC have a cryostatting cooling capacity system deficit of between 8 and 75%. In multi-seat CPC cooling capacity deficit exceeds 50%, which excludes the possibility of obtaining a significant therapeutic effect, as is confirmed by the results of independent studies that show that the procedures in multi-seat CTC safeguards skin from frigorism only up to 14°C, while at the same time for effective OKV frigorism of the skin surface is necessary to a temperature of less than about 2°C. Prior to research on the effectiveness of OKV, it is necessary to assess the energy consumption conformity of cryotherapy equipment. Conclusion. For the successful implementation of OKV in medicine and sport, it is necessary to increase energy efficiency and optimise cryotherapeutic temperature control settings. A cryotheraputic complex should safeguard such physical conditions in such a way that the body surface is frigerised to a temperature of less than about 2°C. The cryostatting patient cabin system cooling capacity should provide heat removal from the surface of the patient's skin with an intensity of no lower than 3.35 kW/m2. For intensive heat removal from the patient's body surface the cooling gas temperature must not exceed -130ºC.